Effect of Micro-Arc Oxidation Coatings Formed at Different Voltages on the In Situ Growth of Layered Double Hydroxides and Their Corrosion Protection. Issue 7 (1st May 2018) - Zhang, Gen; Wu, Liang; Tang, Aitao; Pan, Huiling; Ma, Yanlong; Zhan, Qin; Tan, Qiyang; Pan, Fusheng; Atrens, Andrej
Abstract : In the present work, for the first time micro-arc oxidation (MAO) coatings were produced at different voltages on the magnesium alloy AZ31, leading to the formation of MAO coatings with different properties (e.g. composition, structure and morphology). Then, we studied MgAl layered double hydroxides (LDHs) grown in-situ on MAO coatings. The properties of final composite coatings were largely determined by the dissolution of the MAO coating, and the final composite coatings significantly increased in thickness with the thickest one being 18.0 μm. The corrosion protection was investigated using EIS, hydrogen evolution tests and immersion tests. Due to a synergistic effect of LDHs and spinel, MAO coating formed at the highest production voltage, modified with LDHs, provided the better corrosion protection.